Scene Remodeling and Digital Empowerment: An Analysis of the Implementation Paths and Strategies for Foshan ‘Kung Fu’ and ‘Lion Dance’ IP-driven Integration of Culture, Commerce, and Tourism - He, Dongjin; Zou, Taoyu; Zhou, Jiajun (International Journal of Materials Science and Technology Studies, 2025)
Against the contemporary backdrop of converging digital and experience economies, the value realization pathways for traditional cultural IP are undergoing profound transformations. As cultural IPs with significant international influence, Foshan's "Kung Fu" and "Lion Dance" possess a solid foundation for integrated development in culture, commerce, and tourism. However, they still face practical bottlenecks such as solidified consumption scenes, superficial experience models, and lagging digital applications, which constrain the deep release of their value potential. This paper, using scene theory and digital empowerment theory as its core analytical framework, systematically explores two core implementation paths to drive the value chain leap of Foshan's "Kung Fu" and "Lion Dance" IP. The study argues that the key to breaking through the current predicament lies in implementing a dual-drive strategy of "scene remodeling" and "digital empowerment." The scene remodeling path advocates for transcending traditional "tourist spot" thinking by transforming static cultural landmarks into dynamic, deeply engaging "experience fields" through the narrativization, immersion, and lifestyle integration of physical spaces, thereby activating and enhancing existing resources. The digital empowerment path emphasizes leveraging cutting-edge technologies like virtual reality (VR), augmented reality (AR), and big data to break through physical time-space constraints, creating entirely new virtual consumption scenes and interactive experience models to unlock incremental value. To ensure the effective implementation of this dual-drive strategy, it must be supported by a cross-disciplinary industrial ecosystem, a training system for composite talent, an IP protection mechanism for the digital age, and targeted policy guidance. This research aims to provide a theoretically profound and practically operable set of pathway solutions and strategic references for the deep integrated development of Foshan's "Kung Fu" and "Lion Dance" IP, as well as for similar cultural IPs in China.